Response-based tuning of a negative capacitance shunt for vibration control. (September 2014) - Beck, Benjamin S; Cunefare, Kenneth A; Collet, Manuel
The control of vibrating structures using piezoelectric elements attached to simple control circuits, known as shunts, is a widely studied field. Many different shunt circuits have been researched that have been shown to obtain effective performance in both narrow and broadband frequency ranges. Yet, the choice for the exact parameters of the circuit elements for these vibration-suppressing shunts can be found by various methods. In this study, a new method of selecting the circuit parameters of a negative capacitance shunt is presented. The method predicts the magnitude of the strain-induced voltage caused by the vibrating substrate computed from a single voltage measurement. Therefore, minimizing the strain-induced voltage will mean that the deflection of the structure is also minimized. The tuning theory is confirmed experimentally, which validates that it is possible to experimentally obtain the shunt parameters that produce maximum control through measurement of the shunt response. The suppression ability of the shunt is also compared to the maximum power dissipated. It is found that at high frequency, the parameters that cause maximum power dissipated obtain maximum suppression, but there is no correlation between maximum power dissipated and maximum suppression at low frequency.